2003
DOI: 10.1038/sj.onc.1206700
|View full text |Cite
|
Sign up to set email alerts
|

RAF antisense oligonucleotide as a tumor radiosensitizer

Abstract: The RAF-1 serine-threonine kinase plays a central role in signal transduction pathways involved in cell survival and proliferation. The concept of RAF-1-targeted disruption of cell signaling for therapeutic purposes was first advanced in 1989 with the demonstration of tumor growth inhibition in athymic mice and radiosensitization of human squamous carcinoma cells transfected with a vector expressing antisense cDNA. However, the clinical application of antisense strategies has awaited the development of improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 118 publications
(101 reference statements)
0
40
0
Order By: Relevance
“…The presence of a carrier such as lipofectin is critical to the activity of these agents in vitro, and even if cells are transfected in vivo in the absence of a carrier, it is quite likely that approaches such as liposomal encapsulation will enhance drug delivery. 21 Finally, because the cytostatic effects produced by ISIS 5132 as a single agent are enhanced by combination with cytotoxic agents, combination strategies should be further evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a carrier such as lipofectin is critical to the activity of these agents in vitro, and even if cells are transfected in vivo in the absence of a carrier, it is quite likely that approaches such as liposomal encapsulation will enhance drug delivery. 21 Finally, because the cytostatic effects produced by ISIS 5132 as a single agent are enhanced by combination with cytotoxic agents, combination strategies should be further evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these agents have entered clinical trials, such as small molecule Raf-1 kinase inhibitor, Bay43-9006, for renal and non-small-cell lung cancers. Although combination therapy with Raf-1 antisense ODNs (in complex with liposomes) together with radiation in a preclinical study inhibited tumor growth with little toxicity, 6 there were with liposomal Raf-1 antisense ODN complexes significant dose-limiting complications, minimal to modest Raf-1 mRNA reductions, and no objective tumor response in a phase 1 clinical trial. 26 Another gene therapy approach showed that a plasmid encoding a dominantnegative Raf-1 resulted in regression of primary and metastatic tumors after one systemic injection in a preclinical study.…”
Section: Raf-1 Inhibits Tumor Growth Q Leng and Aj Mixsonmentioning
confidence: 99%
“…Introduction of various 2 0 -O methyl modifications at selected positions in several siRNAs improved their stability in serum but did not decrease their activity. 36 Although unmodified siRNA was completely degraded within 15 minutes upon exposure to serum, certain 2 0 -O methyl substitutions within 6 This radiation therapy may be particularly effective in controlling local tumors such as occur in brain cancer. Although radiation with intratumoral injections is likely to show a synergistic effect, we are also interested in determining whether systemic injections of Raf-1 siRNA with radiation will have a synergistic antitumor effect.…”
Section: Raf-1 Inhibits Tumor Growth Q Leng and Aj Mixsonmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, nucleotides that contain a sequence encoding for specific proteins or hormones can be introduced into target cells and the cell machinery can be exploited to produce the desired proteins. Alternatively, nucleotides that contain a sequence complementary to a specific gene or mRNA can be used to trigger their degradation and return abnormal gene expression to a desired state in approaches such as antisense therapies and interference therapies (siRNA) 102,103 . These nucleotide therapies can potentially alter cellular activities over longer periods of time compared with protein therapies.…”
Section: Cellular Niche and Nucleotide Therapiesmentioning
confidence: 99%